PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT ANDALAN DUTA EKA NUSANTARA TANGERANG SELATAN - Reza Fikri Maulana; Fatimah (Journal of Research and Publication Innovation, 2025)
The purpose of this study is to determine the Influence of Motivation and Work Environment on Employee Performance at PT Andalan Duta Eka Nusantara South Tangerang, both partially and simultaneously. This research method uses a quantitative method with an associative method, data collection used is a questionnaire with a sample of 90 respondents. Data analysis techniques used are: data validity test, reliability test, classical assumption test, simple linear regression test, multiple linear regression test, and hypothesis test. The results obtained in the study based on the t-test on the Motivation variable t count (4.522> 1.987) are supported by the ρ value <Sig.0.05 or (0.001 <0.05) meaning that Motivation (X1) partially has a significant effect on Employee Performance (Y) and the work environment variable (X2) t count (9.006> 1.987) and is supported by the ρ value <Sig.0.05 or (0.001<0.05) meaning that the Work Environment (X2) partially has a significant effect on Employee Performance (Y). Meanwhile, based on the results of the F test, it was found that the F count value was 40.391> F table 3.095 with a significance level of 0.001 <0.05, so it can be concluded that Motivation (X1) and Work Environment (X2) simultaneously have a significant effect on Employee Performance (Y) at PT Andalan Duta Eka Nusantara Tangerang Selatan. With a determination coefficient value of 48.1%, while the remainder of (100-48.1%) = 51.9% is influenced by other factors